An urgent seek for S. epidermidis large host range bacteriophages - Melo, Luís Daniel Rodrigues (2011)
Staphylococcus epidermidis was considered a commensal inhabitant of the human skin and mucous membranes, however has recently emerged as a frequent cause of nosocomial infections, predominantly in patients with indwelling medical devices. Although, S. epidermidis infections only rarely develop into life-threatening diseases, their frequency, and the fact that they are extremely difficult to treat represents a very serious burden for the public health system. This has been related with its ability to adhere to the surfaces of the indwelling medical devices and with the formation of biofilms. The importance of biofilms in the pathogenesis of the S. epidermidis infections is becoming more understandable, consequently several studies are needed, in order to control biofilm formation or remove them from surfaces. Phages have emerged as potential solutions for this problem. However, the majority of the described staphylococcal phages are temperate. Our aim is to search for virulent phages with broad host range for S. epidermidis biofilm therapy. In different attempts, using hospital effluents we were not able to isolate any phage with activity against 40 clinical S. epidermidis isolates with different genetic profiles. With the same approach and using wastewater treatment plants raw effluents 5 different phages were isolated. These phages present different lytic spectra (ranging from 46% to 95% of positive results). Currently, further characterization of these isolated phages is being performed (Transmission Electron Microscopy, SDS-PAGE, RFLP). Preliminary results have shown that in some strains one of the phages is able to cause a 6 Log CFU/ml reduction of the cell titre in <2h for exponential cells and <4h for stationary cells, using a MOI of 1. This phage has also the capacity of reducing the biomass of 24h biofilms (2 LogCFU/ml reduction in some strains). These are promising results, since that phage 1 presents a broad host range and ability to control S. epidermidis biofilms. Ongoing studies are now being performed with the 4 other phages, with the ultimate goal to have a phage cocktail to be used against S. epidermidis biofilm infections.